Revolution in the contemporary Muslim world : review of the 1979 Iran’s Revolution and the 2011 Arab Uprisings - Mohd Irwan Syazli Saidin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article reviews the two major revolutionary events occurred in the Muslim world- the 1979 Iran’s Revolution and the 2011 Arab Uprisings. In particular, it highlights the snapshots of events’ background and examines the factors that ignited the mass uprisings, both in Iran in 1979 and selected countries in the Middle East and North Africa in 2011. These two momentous events were significant in the context of Muslim politics as the nature and outcome of these events shared several common aspects for instance the elements of popular mass protest to topple an autocratic regime, ‘exports’ of the revolution to the global Muslim community as well as the prospect for political change in the countries involved. The methodology of this work employs document analysis, predominantly through published reports and secondary sources. This article revealed that serious economic downturn and unemployment crisis, along with the persistence of autocratic leadership and centralisation of power are the core reasons why the Iranian revolutionaries in 1979 and the Arab protesters in 2011 took to the streets to demand economic and political reform as well as an immediate resignation of their respective ruling regime. Regarding the trajectory of post-Arab Uprisings development in Syria, Yemen and Libya, the situation seems unpredictable, let alone to determine the prospect for democratic transition. Contrary to Iran’s case, those few Arab countries in the post-Uprisings are very unlikely to experience any holistic political change in the near future due to the escalation of on-going domestic tensions and global conflicts across the region.